Wireless GSM haze monitoring system - Szeto, Yang Yang (2017)
Haze is a condition in the atmosphere that hinders visibility in an affected area. Malaysia is a recurring country which haze exists and poses a threat to public health. For a country, which is frequented by the occurrence of haze, air quality readings are not easily accessible by the public. Hence, portable units equipped with sensors and communicative devices could be an alternative to acquire the data. With sensory units that can measure temperature, humidity, carbon monoxide level and dust density along with a global system for mobile communication module and radio frequency module, users will be able to receive readings via Global System for Mobile Communications (GSM) for Short Message Service (SMS) or view them from a monitor. This unit comes in a set of two, a monitoring terminal and a monitoring center. All sensor readings will be acquired from the monitoring terminal and be sent to portable monitoring center for a visual display.